Qiraah Ibn Katsir al-Makki: One Meaning of Qur'anic Interpretation Among the Varieties of Recitation - Putri, Nur Azny Agustina; Aditama, Rahmat Yusuf; Fauzia, Namira (Al-Karim: International Journal of Quranic and Islamic Studies, 2023)
Variations in Qur'anic interpretation are complex phenomena influenced by multiple factors, one of which is the diversity of Qira’at (recitations). Among the prominent figures in Qira’at studies is Ibn Kathir al-Makki, whose recitation was transmitted through two primary narrators, Qunbul and al-Bazzi. This study aims to examine the distinctive characteristics of Ibn Kathir al-Makki’s Qira’at and analyze its impact on Qur'anic interpretation, particularly through the narrations of Qunbul and al-Bazzi. This research employs a qualitative approach with a library research method, gathering data from classical and contemporary sources. The study adopts a descriptive-analytical approach to systematically describe and re-examine the influence of Qira’at variations on Qur'anic exegesis. The findings reveal that while Qira’at plays a crucial role in shaping Qur'anic interpretation, not all variations in recitation lead to significant differences in meaning. Some differences in Qira’at impact theological, legal, and linguistic interpretations, while others remain within the bounds of phonetic variation without altering core meanings. This highlights the intricate nature of Qur'anic interpretation and the necessity of considering broader linguistic, contextual, and historical factors in exegetical studies. Theoretically, this study underscores the importance of Qira’at in the development of Qur'anic hermeneutics and the methodology of tafsir. Its contribution lies in providing a deeper understanding of how Ibn Kathir al-Makki’s Qira’at, as transmitted by Qunbul and al-Bazzi, influences Qur'anic interpretation, thereby enriching scholarly discourse on the intersection between recitation and exegesis. Contribution: This study contributes to Qur'anic studies by demonstrating the nuanced relationship between Qira’at and interpretation, particularly in Ibn Kathir al-Makki’s recitation, highlighting its selective yet significant impact on exegetical discourse.